Pangenome-level analysis of nucleoid-associated proteins in the Acidithiobacillia class: insights into their functional roles in mobile genetic elements biology - Beard, Simón; Moya-Beltrán, Ana; Silva-García, Danitza; Valenzuela, Cesar; Pérez-Acle, Tomás; Loyola, Alejandra; Quatrini, Raquel (Frontiers in Microbiology, 2023)
Mobile genetic elements (MGEs) are relevant agents in bacterial adaptation and evolutionary diversification. Stable appropriation of these DNA elements depends on host factors, among which are the nucleoid-associated proteins (NAPs). NAPs are highly abundant proteins that bind and bend DNA, altering its topology and folding, thus affecting all known cellular DNA processes from replication to expression. Even though NAP coding genes are found in most prokaryotic genomes, their functions in host chromosome biology and xenogeneic silencing are only known for a few NAP families. Less is known about the occurrence, abundance, and roles of MGE-encoded NAPs in foreign elements establishment and mobility. In this study, we used a combination of comparative genomics and phylogenetic strategies to gain insights into the diversity, distribution, and functional roles of NAPs within the class Acidithiobacillia with a special focus on their role in MGE biology. Acidithiobacillia class members are aerobic, chemolithoautotrophic, acidophilic sulfur-oxidizers, encompassing substantial genotypic diversity attributable to MGEs. Our search for NAP protein families (PFs) in more than 90 genomes of the different species that conform the class, revealed the presence of 1,197 proteins pertaining to 12 different NAP families, with differential occurrence and conservation across species. Pangenome-level analysis revealed six core NAP PFs that were highly conserved across the class, some of which also existed as variant forms of scattered occurrence, in addition to NAPs of taxa-restricted distribution. Core NAPs identified are reckoned as essential based on the conservation of genomic context and phylogenetic signals. In turn, various highly diversified NAPs pertaining to the flexible gene complement of the class, were found to be encoded in known plasmids or larger integrated MGEs or present in genomic loci associated with MGE-hallmark genes, pointing to their role in the stabilization/maintenance of these elements in strains and species with larger genomes. Both core and flexible NAPs identified proved valuable as markers, the former accurately recapitulating the phylogeny of the class, and the later, as seed in the bioinformatic identification of novel episomal and integrated mobile elements.